Does high intensity interval training (HIIT) have an effect on young swimmers' performance? Manuscript and coaching applications - Papadimitriou, K.; Savvoulidis, S. (Journal of Swimming Research, 2017)
Swimming in different high intensities and intervals (HIIT) is a type of exercise that can provide several improvements for swimming training. The aim of this review is to find out if HIIT swimming training is safe and beneficial for young swimmers. 43 studies from different HIIT`s parameters were used to create this review. To be more specific, studies were used on HIIT`s effects in human physiology, different types of rest protocols of HIIT, and other studies were carried out on the actual performance not only in swimming, but in other sports as well. The results showed us that HIIT can have a positive effect on the majority of physiological parameters including oxygen uptake, and muscle fibers. Moreover, the same positive effects can be found in the performance of soccer, rowing, kayak, cycling and in track athletes as the improvements reached from 6, 7 to 20%. These improvements also had effects on average recovery time between 60 to 120 seconds. To sum up, the HIIT technique showed us that it can provide benefits not only in young swimmers` performance but in most of the studies that were carried out. Importantly, we recommend that further studies on the HIIT`s effects in young swimmers` performance must be continued so as to determine if this training method can continue producing improvements while reducing the training load.